2001
DOI: 10.1002/ar.10027
|View full text |Cite
|
Sign up to set email alerts
|

Development of the rat sublingual gland: A light and electron microscopic immunocytochemical study

Abstract: Cell differentiation in the rat sublingual gland occurs rapidly and is largely complete by birth. To study differentiation of the serous and mucous cells of the sublingual gland, we used antibodies to the secretory proteins CSP-1, SMGB, PSP, and SMGD, and sublingual mucin as specific cell markers. Glands from rats at ages 18, 19, and 20 days in utero, and postnatal days 0, 1, 5, 9, 14, 18, 25, 40, and 60 were fixed and prepared for morphological analysis and immunocytochemical labeling. At age 18 days in utero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 30 publications
8
38
0
Order By: Relevance
“…Therefore, cell death appeared to be a rare event. Wolff et al (2002) also suggested that mucous and serous cells of the rat sublingual grand differentiate from separate lineages. Although we found no evidence to support their hypothesis, we clarified the granule types and their morphological changes in terminal-cluster and acinar cells in the late pre-and early postnatal rat sublingual gland.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, cell death appeared to be a rare event. Wolff et al (2002) also suggested that mucous and serous cells of the rat sublingual grand differentiate from separate lineages. Although we found no evidence to support their hypothesis, we clarified the granule types and their morphological changes in terminal-cluster and acinar cells in the late pre-and early postnatal rat sublingual gland.…”
Section: Discussionmentioning
confidence: 98%
“…Ball et al (1993) and Mirels et al (1998) also demonstrated that highly electron-dense granules in secretory cells from the early postnatal mouse parotid gland, and in cells from the serous demilune of the mature rat sublingual gland contain protein B1. Furthermore, Wolff et al (2002) showed that by age 20 days in utero, mucous cells in the rat sublingual gland have granules labeled with antimucin, and serous cells have numerous granules containing CSP-1, SMGB, PSP, and SMGD. These results suggest that some proteins are present throughout Type I and II granules and in the electron-dense portion of Type III granules.…”
Section: Discussionmentioning
confidence: 99%
“…The formation and acinar differentiation of the mixed secretion salivary glands occur mainly prenatally [25,26], and the intra-uterine forming epigenetic changes in metabolism and the morphofunctional state of the glands can persist for life and affect the cariogenic situation in oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of developmental changes in the ultrastructure and peroxidase activity in rat sublingual and submandibular gland acinar cells also suggest that the serous cells differentiate into seromucous or mucous cells during histogenesis of the endpieces [6,7]. In a different interpretation of an immunocytochemical study of the expression pattern of several secretory proteins in developing rat sublingual glands, Wolff et al [9] suggested that the serous and mucous cells differentiate via separate cell lineages. It is necessary to examine the relationship between their expression pattern and proliferative activity of the secretory cells.…”
Section: Resultsmentioning
confidence: 99%